Factors Influencing the Sex Ratio at Birth in India: A New Analysis based on Births Occurring between 2005 and 2016 - Singh, Abhishek (Stud Fam Plann, 2021)
Previous research on sex ratio at birth (SRB) in India has largely relied on macro‐analysis of census data that do not contain the breadth of factors needed to explain patterns in SRB. Additionally, no previous research has examined the differentiation of factors associated with SRB across birth orders, a key determinant in societies affected by son preference. This study aims to fill these gaps using micro‐data related to 553,461 births occurring between 2005 and 2016 collected as part of the 2015–2016 National Family Health Survey. Analyses used multivariable logistic regressions stratified by birth order to examine associations with SRB at the national level. The SRB at birth order 1 was outside the biological normal limit, and generally increased with birth order. First births in households with wealth in the middle and richest quintiles, with mothers who desired a higher ideal number of sons than daughters, and in lower fertility communities had a higher probability of being male. Most SRB correlates were visible at birth orders 3 or higher. Programs and policies designed to address India's male‐skewed SRB must consider the diverse factors that influence SRB, particularly for higher order births.